Comprehensive phenotyping of human peripheral blood B lymphocytes in pathological conditions. Issue 2 (1st December 2021) - Carsetti, Rita; Corrente, Francesco; Capponi, Claudia; Mirabella, Mattia; Cascioli, Simona; Palomba, Patrizia; Bertaina, Valentina; Pagliara, Daria; Colucci, Manuela; Piano Mortari, Eva
Abstract: Several diseases are associated with alterations of the B‐cell compartment. Knowing how to correctly identify by flow cytometry the distribution of B‐cell populations in the peripheral blood is important to help in the early diagnosis. In the accompanying article we describe how to identify the different B‐cell subsets in the peripheral blood of healthy donors. Here we show a few examples of diseases that cause dysregulation of the B‐cell compartment.